Structural performance of cellular stainless-steel beams with varied web hole diameters under fire conditions: finite element analysis and experimental insights - Asmadi, Muhammad Irfan Ahlami; Ismail, Ruqayyah; Ahmad Zakwan, Fariz Aswan; Muhammad Rashid, Raizal Saifulnaz; Zulkifli, Syaza Nur Iylia (National University of Malaysia, 2025)
This study focuses on the structural behaviour of cellular stainless-steel beams (CSSBs) with different diameter web holes at elevated temperatures using an experimental-numerical approach. Key parameters such as stiffness, load-bearing capacity, and stress distribution were investigated through three-point bending and fire heating tests in accordance with ISO 7438 and ISO 834 standards, respectively. Using ABAQUS, a two-step Finite Element Analysis (FEA) framework was constructed, with thermal and structural analyses conducted in succession, simulating experimental conditions as closely as possible. Results showed that smaller web hole diameters increased stiffness and load bearing capacity but increased the weight of material. On the other hand, larger holes were more materials efficient but greatly increased stress concentrations, resulting in an overall performance drop of the structure. The parametric studies highlighted the most critical trade-off, between structural integrity and materials efficiency, and the need for careful and optimal web hole design. Although no direct comparison at room temperature was made, qualitative trends agreed with previous studies and confirmed the validity of the numerical model. This study highlights the need for structural design to ensure a balance between web hole size, fire resistance and load-bearing capacity. This approach allows for a more targeted focus on understanding the specific design considerations necessary for enhancing the fire resistance of stainless-steel beams, as the results can be used to support the development of fire-safe design guidelines specifically for this type of beam.